Variable frequency drive (VFD) considerations for irrigation - Burt, C. M., author; Gaudi, F., author; Piao. X., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2007)
This paper covers considerations in VFD applications, plus details a study performed by the Irrigation Training and Research Center (ITRC) to determine motor performances under varying speeds (controlled by a VFD) and loads.
USCID fourth international conference
Not digitized by CSUL Digital Services.
Presented at the Role of irrigation and drainage in a sustainable future: USCID fourth international conference on irrigation and drainage on October 3-6, 2007 in Sacramento, California.
Keywords: variable frequency drives; energy efficiency; motors; electricity; pumps; power usage; irrigation